Estrutura genética entre os boto-cinzas (Sotalia guianensis, Van Bénéden 1864) do litoral sul da Bahia e do Espírito Santo - Mendes, Fabio Ribeiro (2019)
Sotalia guianensis is a small cetacean of the Delphinidae family distributed continuously along the coastal region of Central and South America. This study evaluated a possible genetic structure between gray porpoises off the coast of Espirito Santo and southern Bahia. A total of 203 individuals were analyzed: 18 from SBA-A (southern Bahia a), 75 from SBA-b to NRD (southern Bahia b to the north of Rio Doce) and 110 from SRD to South ES (South ES of the Doce River). A 409bp fragment from the control region of mitochondrial DNA was obtained. A total of 18 haplotypes were found, seven of them exclusive to SBA-a, two to SRD to the south of ES. The haplotypic and nucleotide diversity were respectively for each region, SBA-a (h = 0.8889; π = 0.266521), SBA-b for NRD (h = 0.8071; π = 0.1449862) and SRD for the South ES (h = 0.8359; π = 0.179052). It was possible to evidence the genetic structure between the three regions, being higher between SBA-a and SBA-b until NRD (Fst = 0.14163 p